Mongolia Economic Update, December 2014 - Lee, Taehyun; Shiilegmaa, Altantsetseg; Batsuuri, Davaadalai (World Bank Group, Washington, DC, 2015)
In 2014, economic growth slowed as it began to adjust to unsustainable economic imbalances. Real GDP growth softened to 7 percent in the first 9 months, from 12.8 percent in the previous year. Despite strong mining production growth of 26 percent, the growth of the non-mining sector of the economy dropped to 2 percent in the third quarter from 17.4 percent a year ago. Investment sharply fell amidst declining FDI and weakening business prospects. Consumption remains relatively strong but is also gradually softening. The growth effect from stimulus measures of the last year is also wearing off in 2014 as large liquidity support from the central bank cannot be sustained in the wake of high inflation and external vulnerabilities. The current account deficit is narrowing significantly to around 11 percent of GDP from almost 30 percent in the previous three years, due to import contraction over 16 percent and stronger copper exports. However, a significant external financing gap continues amidst declining foreign investment, reducing internal reserves to less than three months import cover. Inflation remains in double digits after a strong credit boom in 2014 and continuous currency depreciation. Economic growth is likely to continue to soften in 2015 as the economy remains under pressure from the external imbalance and high inflation. To help achieve the goal of the new Solutions-oriented Government to overcome economic challenges and build a sound economic management system, the following policy actions are recommended to be considered in the economic policy framework: (1) Consolidate the off-budget spending made through the DBM into the budget; (2) prepare a credible and realistic fiscal consolidation plan to reduce the deficit; (3) monetary policy should be tightened; (4) further quasi-fiscal activities need to be avoided; and (5) the exchange rate should be left flexible.